Neuropedagogy: Preconditions for Application of Neuroscience Results in the Education Process While Providing Feedback - , Ausra Kazlauskiene; Irina Barabanova, (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
As the progress in scientific areas is rapidly evolving, increasingly more and more researchers representing different areas of sciences are searching for the most suitable solution to help balance societal development and potential of personality education. New knowledge making the largest impact on the development of science, society, culture, perception and countries occurs at the intersection of different disciplines. Even though the pedagogy science is independent, it can successfully develop only in relation to other sciences because various sciences focus on its object. Rapid development of neurosciences currently meets the grounding function of many other sciences. The education science is concerned about understanding of how we learn, how we teach; whereas neuroscience seeks answering a question of how brain constructs new learning and how brain organises and processes information, how the processes taking place in brain contribute to the process of teaching and learning. Effectively provided feedback has the largest effect on learning achievement and progress. The following aspects are highly important for effective development of feedback in the education process: emotional environment and sociocultural aspects. Therefore, research studies in neurosciences carried out in this context ground the identification of the results to facilitate the development of approaches, techniques of feedback provided in the process of (self-) education.